PENGARUH AGITASI DAN WAKTU FERMENTASI PADA PEMBUATAN BIOETANOL DARI PATI SINGKONG KARET (Manihot glaziovii) - ., Yuniar; Aznury, Martha; Resky, Resky (Politeknik Negeri Sriwijaya, 2020)
Rubber Cassava (Manihot glaziovii) is a tuber that is not a food ingredient because it contains the chemical element cyanide (HCN) which is toxic. The starch content in sweet potatoes reaches 98.5%. This study aims to determine the effect of agitation and fermentation time on the levels of biethanol using a 3 liter fermentor substrate used is cassava rubber (Manihot glaziovii). The process of making starch by cutting and peeling rubber cassava and then washing it with clean water after that shredded it with grated while adding water after grating the cassava pulp porridge at a temperature of 600C so as to get the starch. The dried cassava rubber starch was sieved to obtain a more homogeneous starch particle size. Furthermore, the hydrolysis process involves mixing 800 grams of cassava rubber starch with 2 liters of distilled water. In the fermentation process variation of stirring speed and time of fermentation. The results showed that The best stirring speed in this research is 300 rpm and the best fermentation time is 48 hours with bioethanol levels obtained at 10%.